Association of Angiotensin-Converting Enzyme Genotype, Insertion/Deletion Polymorphism and Saphenous Vein Graft Atherosclerosis in Iranian Patients - Zeinali,Neda (2015)
ABSTRACT OBJECTIVE: The aim of this study was to evaluate possible interactions among Angiotensin-I converting enzyme genotype, insertion/deletion polymorphism and atherosclerosis of vein grafts in Iranian patients, and characterize their clinical and demographic profile. METHODS: In this cross-sectional study, patients who underwent coronary artery bypass graft surgery more than five years ago, were included for angiographic analysis. Atherosclerosis was determined by quantitative angiography and adjusted Gensini score. The gene angiotensin converting enzyme I/D polymorphism was detected by polymerase chain reaction. RESULTS: A total of 102 patients participated in this study. Eighty-four patients were male. The frequency distribution of DD, ID and II polymorphism were 23.6%, 62.7% and 13.7% respectively. There were no differences among genotypic groups in age, sex, number of risk factors, number of vein grafts and months since bypass surgery. According to adjusted Gensini score [0.18±0.12 (II) vs. 0.11±0.09 (ID) and 0.1±0.09 (DD) P=0.021] the II genotype was associated with severity of vein graft atherosclerosis. CONCLUSION: Although there are conflicting results about gene angiotensin converting enzyme I/D polymorphism and the degree of venous bypass graft degeneration, this study suggests an association between ACE genotype II and atherosclerosis of saphenous vein grafts, however, large samples considering clinical, demographic and ethnic profile are necessary to confirm these results.